Group IV humpback whales: their status from aerial and landbased surveys off Western Australia, 2005 - Paxton, Charles G.M.; Hedley, Sharon l.; Bannister, John l. (J. Cetacean Res. Manage., 2020)
Single platform aerial line transect and land-based surveys of Southern Hemisphere Group IV humpback whales were undertaken to provide absolute abundance estimates of animals migrating northward along the western Australian coast during June–August 2005. The aerial survey was designed to cover the whole period of northward migration but the resulting estimates from that survey alone could only, at best, provide relative abundance estimates as it was not possible to estimate g(0), the detection probability along the trackline, from the data. Owing to logistical constraints, the land-based survey was only possible for a much shorter period (two weeks during the expected peak of the migration in mid-July). This paper proposes three methods that utilise these complementary data in different ways to attempt to obtain absolute abundance estimates. The aerial line transect data were used to estimate relative whale density (for each day), allowing absolute abundance from the land-based survey to be estimated for the short period of its duration. In turn, the land-based survey allowed estimation of g(0) for the aerial survey. Absolute estimates of abundance for the aerial survey were obtained by combining the g(0) estimate with the relative density estimates, summing over the appropriate number of days. The most reliable estimate of northward migrating whales passing the land station for the period of the land-based survey only was 4,700 (95% CI 2,700–14,000). The most reliable estimate for the number of whales passing through the aerial survey region for the duration of that survey (55 days from June through to August) was 10,300 (95% CI 6,700–24,500). This is a conservative estimate because the duration of the aerial survey was almost certainly shorter than the period of the migration. Extrapolation beyond the end of this survey was considered unreliable, but abundance from the estimated start of the migration to the end of the survey (87 days from mid-April to August) was estimated to be 12,800 (95% CI 7,500– 44,600). The estimated number of whales depends crucially on the assumed migration and period of migration. Results for different migration parameters are also presented. The point estimates of abundance, whilst higher than those from a previous survey in 1999 (when adjusted for survey duration) are not significantly so. The peak of the whales’ distribution was found at c.90m water depth.